Tungsten diselenide / nitrogen-doped porous carbon composite material, modified diaphragm and preparation method and application thereof

By coating the separator of the sodium-sulfur battery with tungsten diselenide/nitrogen doped porous carbon composite material, the loss of active substances and battery capacity attenuation caused by the polysulfide shuttle effect is solved, and the stability and electrochemical performance of the battery are significantly improved.

CN119774556AActive Publication Date: 2025-04-08CHINA ENERGY GRP NINGXIA COAL IND CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411743248.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-08
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The shuttle effect of polysulfides in existing sodium-sulfur batteries leads to serious losses of active substances and rapid attenuation of battery capacity.

Method used

The separator is modified by using tungsten diselenide/nitrogen doped porous carbon composite material. By filling tungsten diselenide in the porous channel of nitrogen doped porous carbon, polar tungsten diselenide is used to form bonds with soluble polysulfide, and polysulfide is adsorbed through the van der Waals force and active sites of porous carbon to inhibit the shuttle effect.

Benefits of technology

It effectively inhibits the shuttle effect of polysulfides, reduces the loss of active substances, and significantly enhances the stability and electrochemical properties of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774556A_ABST
    Figure CN119774556A_ABST
Patent Text Reader

Abstract

The invention provides a tungsten diselenide / nitrogen-doped porous carbon composite material, a modified diaphragm and a preparation method and application of the tungsten diselenide / nitrogen-doped porous carbon composite material. The tungsten diselenide / nitrogen-doped porous carbon composite material comprises nitrogen-doped porous carbon, and pores of the nitrogen-doped porous carbon are filled with tungsten diselenide; wherein the mass ratio of the tungsten diselenide to carbon in the nitrogen-doped porous carbon is (10-30): (90-70), and the doping amount of nitrogen in the tungsten diselenide / nitrogen-doped porous carbon composite material is 1-5at.%. The diaphragm is modified through the tungsten diselenide / nitrogen-doped porous carbon composite material, so that the shuttle effect caused by dissolving polysulfide into an organic electrolyte in the room-temperature sodium-sulfur battery circulation process is inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage materials, and in particular to a tungsten diselenide / nitrogen-doped porous carbon composite material, a modified diaphragm, and a preparation method and application thereof. Background Art

[0002] In order to mitigate the serious climate change and environmental pollution caused by the burning of fossil fuels, it is urgent to innovate battery technology and develop advanced electrode materials. Studies have shown that room temperature sodium-sulfur batteries have the advantages of high theoretical energy density, low cost and environmental friendliness, which brings them broad practical application prospects. Therefore, they are considered to be the next generation of energy storage systems with great commercial value. Unfortunately, its commercialization path still faces problems such as actual energy density far lower than the theoretical value, short cycle life and poor safety performance. First, the positive electrode sulfur (5×10 -30 S cm -1 ) and its discharge product sodium sulfide (Na2S2 / Na2S) have poor conductivity, which leads to low reaction activity of sodium-sulfur batteries; secondly, the positive electrode sulfur will undergo severe volume expansion during the charge and discharge process, which makes the substrate structure easy to crush and the battery cycle stability is poor; finally, the sodium polysulfide generated during the sodium-sulfur battery reaction is easily dissolved in the electrolyte to cause a "shuttle effect", resulting in serious loss of active materials and rapid decay of battery capacity. Sodium polysulfide is easily soluble in the electrolyte and diffuses to the sodium negative electrode to cause side reactions, causing the shuttle effect. The irreversible loss of active materials is the main reason for the above problems. The glass fiber diaphragm has a rich pore structure and a large pore size, and has a weak inhibitory effect on the shuttle effect of sodium polysulfide. Therefore, it is necessary to modify the glass fiber diaphragm to meet the needs of high specific energy and long life room temperature sodium-sulfur batteries. The introduction of polar materials can inhibit the dissolution of soluble polysulfides in the electrolyte, that is, reduce the content of polysulfides in the electrolyte, thereby improving the utilization rate and cycle life of the positive electrode sulfur. From the perspective of physical constraints applied to glass fiber separators, carbon-based materials have high electrical conductivity, large specific surface area, universal porous structure and low cost, and can play a better role when combined with polar materials.

[0003] However, the way to suppress the shuttling effect of polysulfides in the prior art is to improve the positive electrode material. The preparation process of the positive electrode material is complicated and the performance improvement is not obvious. For example, a heterostructure is constructed to improve the redox reaction kinetics of the sodium-sulfur battery. Na2S / Na2Te@C has the advantages of rich heterogeneous interfaces, high conductivity and porosity, which can promote electron / ion diffusion and provide high catalytic activity. The Na2S@Na2Te heterostructure embedded in the carbon structure is intended to effectively suppress the shuttling effect of polysulfides. The prior art discloses a tantalum-based metal nitride porous carbon sphere based on defect engineering as a sulfur positive electrode material for a sodium-sulfur battery, which controllably introduces defects to prepare a defective tantalum nitride porous carbon sphere composite material. The prior art also discloses a cobalt-based metal compound mesoporous carbon sphere composite material and a preparation method thereof as a sodium-sulfur battery positive electrode material; the method uses the composite material Co-SC@MC to prepare a sodium-sulfur battery positive electrode material, which has a high discharge specific capacity, long cycle stability and excellent rate performance. There are also some methods in which the tea residue powder with lignin removed is treated and evenly mixed with solid sublimated sulfur in proportion, and reacted at 140℃~160℃ for 10h~15h and then heated to 180℃~300℃ to remove surface sulfur to obtain sodium-sulfur battery positive electrode material, which can improve the specific capacity of sodium-sulfur batteries.

[0004] At present, there are few studies on improving battery performance by inhibiting the sodium polysulfide shuttle effect through modified diaphragms. Although the prior art discloses a method for preparing a diaphragm modification material, in which metal sulfide particles are composited with porous carbon by load annealing, and the resulting composite material is coated on the surface of a commercial diaphragm to obtain a diaphragm modification layer, in lithium-sulfur and sodium-sulfur batteries, the "shuttle effect" of polysulfides can be inhibited by capturing the catalytic conversion mechanism, thereby improving the life of the battery. However, carbon materials are non-polar materials and can only adsorb polysulfides through weak intermolecular forces, and the effect is limited.

[0005] In view of this, this application is hereby filed. Summary of the invention

[0006] The main purpose of the present invention is to provide a tungsten diselenide / nitrogen-doped porous carbon composite material, a modified diaphragm, and a preparation method and application thereof, so as to solve the problem in the prior art that the shuttling effect of polysulfides in sodium-sulfur batteries leads to serious loss of active materials and rapid attenuation of battery capacity.

[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a tungsten diselenide / nitrogen-doped porous carbon composite material is provided, wherein the tungsten diselenide / nitrogen-doped porous carbon composite material comprises nitrogen-doped porous carbon, and the pores of the nitrogen-doped porous carbon are filled with tungsten diselenide; wherein the mass ratio of tungsten diselenide to carbon in the nitrogen-doped porous carbon is (10-30): (90-70), and the doping amount of nitrogen in the tungsten diselenide / nitrogen-doped porous carbon composite material is 1-5 at.%.

[0008] Furthermore, the particle size of the tungsten diselenide / nitrogen-doped porous carbon composite material is 0.5-1.0 μm.

[0009] Furthermore, the specific surface area of ​​nitrogen-doped porous carbon is 100-500 m 2 / g.

[0010] Furthermore, the pore volume of nitrogen-doped porous carbon is 0.12 cm 3 / g~0.65cm 3 / g.

[0011] Furthermore, the preparation method of nitrogen-doped porous carbon includes the following steps: mixing porous carbon with melamine, and performing a heat treatment to obtain nitrogen-doped porous carbon.

[0012] Furthermore, the mass ratio of porous carbon to melamine is 1:1-10.

[0013] Furthermore, the temperature of the heating treatment is 800-850° C., and the time of the heating treatment is 4-6 hours.

[0014] According to another aspect of the present invention, there is provided a method for preparing the tungsten diselenide / nitrogen-doped porous carbon composite material provided in the first aspect above, comprising the following steps: providing nitrogen-doped porous carbon, mixing the nitrogen-doped porous carbon, Na2WO4·2H2O, selenium powder, acid solution, and additives, and preparing the tungsten diselenide / nitrogen-doped porous carbon composite material by a solvothermal method.

[0015] Furthermore, the acid solution includes at least one of a hydrochloric acid solution, an acetic acid solution, and a phosphoric acid solution, and further comprises a hydrochloric acid solution.

[0016] Furthermore, the auxiliary agent includes at least one of N2H4·2H2O, carbon disulfide, and quinoline, and further includes N2H4·2H2O.

[0017] Furthermore, the reaction temperature of the solvothermal method is 180-250° C., and the reaction time of the solvothermal method is 10-16 hours.

[0018] Furthermore, the molar ratio of Na2WO4·2H2O to selenium powder is 1:1-5.

[0019] Furthermore, the mass ratio of Na2WO4·2H2O to nitrogen-doped porous carbon is (5-10):1.

[0020] According to the third aspect of the present invention, a modified diaphragm is provided, which includes a diaphragm, and a modified coating is provided on the side of the diaphragm close to the positive electrode. The material of the modified coating includes the tungsten diselenide / nitrogen-doped porous carbon composite material, a conductive agent and a binder provided in the first aspect or the second aspect.

[0021] Furthermore, the loading amount of the tungsten diselenide / nitrogen-doped porous carbon composite material on the diaphragm is 0.2-0.6 mg / cm 2 .

[0022] Furthermore, the conductive agent includes at least one of Super P, activated carbon, and acetylene black; and further, the conductive agent is Super P.

[0023] Furthermore, the binder includes at least one of PVDF, CMC, and SBR; further, the binder is PVDF.

[0024] Furthermore, the material of the diaphragm includes at least one of glass fiber, polypropylene, and polyethylene; further, the material of the diaphragm is glass fiber.

[0025] Furthermore, the mass ratio of the tungsten diselenide / nitrogen-doped porous carbon composite material, the conductive agent, and the binder is (6-8):(3-1):1.

[0026] According to the fourth aspect of the present invention, there is provided a method for preparing the modified diaphragm provided in the third aspect, the preparation method comprising the following steps: mixing a tungsten diselenide / nitrogen-doped porous carbon composite material, a conductive agent, and a binder, and then grinding the mixture, and then dispersing the mixture in a solvent to obtain a modified coating slurry; applying the modified coating slurry to the side of the diaphragm close to the positive electrode, removing the solvent, and obtaining a modified diaphragm.

[0027] Further, the solvent includes at least one of NMP, deionized water, and DMF; further, NMP.

[0028] According to a fifth aspect of the present invention, there is provided a tungsten diselenide / nitrogen-doped porous carbon composite material provided by the first aspect or the second aspect, or a modified diaphragm provided by the third aspect or the fourth aspect for use in a sodium-sulfur battery.

[0029] Applying the technical solution of the present application, the present application modifies the diaphragm by a tungsten diselenide / nitrogen-doped porous carbon composite material to suppress the shuttle effect caused by the dissolution of polysulfides into the organic electrolyte during the cycle of the room temperature sodium-sulfur battery. The tungsten diselenide / nitrogen-doped porous carbon composite material is filled with tungsten diselenide in the pores of the nitrogen-doped porous carbon, wherein the polar tungsten diselenide can form a bond with the soluble polysulfide to limit the shuttling of the polysulfide; at the same time, the porous carbon adsorbs the polysulfide through the van der Waals force and active sites; and the nitrogen doped in the porous carbon can provide more active sites to adsorb the polysulfide, thereby effectively suppressing the "shuttle effect", effectively reducing the loss of active substances, and promoting the significant enhancement of the stability of the battery.

[0030] In addition, the present application obtains a modified diaphragm by coating a modified coating material comprising a tungsten diselenide / nitrogen-doped porous carbon composite material on one side of the diaphragm close to the positive electrode, which can significantly improve the electrochemical performance of a room temperature sodium-sulfur battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0032] Figure 1 A schematic diagram showing the position of the modified separator in the sodium-sulfur battery and the inhibition of the shuttle effect;

[0033] Figure 2 The SEM schematic diagram of the modified glass fiber separator in Example 1 is shown;

[0034] Figure 3 A SEM schematic diagram of the glass fiber separator in Comparative Example 1 is shown. DETAILED DESCRIPTION

[0035] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0036] As analyzed in the background technology of the present application, the prior art has poor effect in suppressing the shuttle effect of polysulfides in sodium-sulfur batteries by improving the positive electrode material, and the use of porous carbon modified membranes to adsorb polysulfides has limited effect. In order to solve this problem, the present application provides a tungsten diselenide / nitrogen-doped porous carbon composite material, a modified membrane, and a preparation method and application thereof.

[0037] In a first typical embodiment of the present application, a tungsten diselenide / nitrogen-doped porous carbon composite material is provided, which includes nitrogen-doped porous carbon, and tungsten diselenide is filled in the pores of the nitrogen-doped porous carbon; wherein the mass ratio of tungsten diselenide to carbon in the nitrogen-doped porous carbon is (10-30): (90-70), and the nitrogen doping amount in the tungsten diselenide / nitrogen-doped porous carbon composite material is 1-5 at.%.

[0038] The present application modifies the diaphragm by a tungsten diselenide / nitrogen-doped porous carbon composite material to suppress the shuttle effect caused by the dissolution of polysulfides into the organic electrolyte during the cycle of the room temperature sodium-sulfur battery. The tungsten diselenide / nitrogen-doped porous carbon composite material is filled with tungsten diselenide in the pores of the nitrogen-doped porous carbon, wherein the polar tungsten diselenide can form a bond with the soluble polysulfide to limit the shuttling of the polysulfide; at the same time, the porous carbon adsorbs the polysulfide through the van der Waals force and the active site; and the nitrogen doped in the porous carbon can provide more active sites to adsorb the polysulfide, thereby effectively suppressing the "shuttle effect", effectively reducing the loss of active substances, and promoting the significant enhancement of the stability of the battery. In addition, by coating the coating material containing the tungsten diselenide / nitrogen-doped porous carbon composite material on the side of the diaphragm close to the positive electrode to obtain a modified diaphragm, the electrochemical performance of the room temperature sodium-sulfur battery can be significantly improved.

[0039] Compared with using a single material (such as only tungsten diselenide or only nitrogen-doped porous carbon), in a battery using a modified separator coated with a tungsten diselenide / nitrogen-doped porous carbon composite material, the sodium ion diffusion coefficient is large and, at the same time, excellent adsorption performance for sodium polysulfide is exhibited.

[0040] Typically but not restrictively, in the tungsten diselenide / nitrogen-doped porous carbon composite material provided in the present application, the mass ratio of the porous carbon in the tungsten diselenide and nitrogen-doped porous carbon is 10:90, 15:85, 20:80, 25:75, 30:70 or a range consisting of any two numerical values; the doping amount of nitrogen in the tungsten diselenide / nitrogen-doped porous carbon composite material is 1at.%, 2at.%, 3at.%, 4at.%, 5at.% or a range consisting of any two numerical values.

[0041] In the present application, "at. %" means atomic percent.

[0042] The porous structure of the porous carbon in nitrogen-doped porous carbon can fill tungsten diselenide in the pores, thereby increasing the active sites, further inhibiting the shuttling of polysulfides, promoting the rapid transmission of electrolytes and ions, and improving the electrochemical performance of the battery. In addition, nitrogen-doped porous carbon with a larger specific surface area can provide a larger reaction interface, promote the adsorption of polysulfides, and enable the battery to have excellent battery capacity retention and cycle stability. In order to further promote the filling of tungsten diselenide in the pores and the adsorption of polysulfides, the specific surface area of ​​the nitrogen-doped porous carbon is preferably 100 to 500 m 2 / g, and the pore volume of nitrogen-doped porous carbon is 0.12 cm 3 / g~0.65cm 3 / g.

[0043] Typically, but not limiting, the specific surface area of ​​nitrogen-doped porous carbon is 100 m 2 / g, 200m2 / g、300m 2 / g, 400m 2 / g、500m 2 / g or a range of values ​​consisting of any two values; the pore volume of nitrogen-doped porous carbon is 0.12cm 3 / g, 0.20cm 3 / g, 0.30cm 3 / g, 0.40cm 3 / g, 0.50cm 3 / g, 0.65cm 3 / g or a range of any two values.

[0044] Since the separator in the battery is a three-dimensional porous membrane, its pore size distribution is 0.3-10 μm. The tungsten diselenide / nitrogen-doped porous carbon composite material is coated on the side of the separator close to the positive electrode. In order to improve its stability as a separator modification material and avoid the battery short circuit caused by the tungsten diselenide / nitrogen-doped porous carbon composite material falling off through the pores of the separator, the particle size of the tungsten diselenide / nitrogen-doped porous carbon composite material is preferably 0.5-1.0 μm.

[0045] Typically but not limiting, the particle size of the tungsten diselenide / nitrogen-doped porous carbon composite material is 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm or a range consisting of any two values.

[0046] In some embodiments, the method for preparing nitrogen-doped porous carbon comprises the following steps: mixing porous carbon with melamine and performing a heat treatment to obtain nitrogen-doped porous carbon. During the preparation process, only a small amount of nitrogen atoms are doped into the porous carbon.

[0047] In order to further promote the formation of nitrogen-doped porous carbon, the mass ratio of porous carbon to melamine is preferably 1:1-10.

[0048] Typically but not limiting, the mass ratio of porous carbon to melamine is 1:1, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or a range consisting of any two values.

[0049] In order to further increase the porosity of the nitrogen-doped porous carbon, the temperature of the heat treatment is preferably 800 to 850° C., and the time of the heat treatment is 4 to 6 hours.

[0050] Typically but not limiting, the temperature of the heating treatment is 800°C, 810°C, 820°C, 830°C, 840°C, 850°C or a range consisting of any two values; the time of the heating treatment is 4h, 4.5h, 5h, 5.5h, 6h or a range consisting of any two values.

[0051] In a second typical embodiment of the present application, a method for preparing a tungsten diselenide / nitrogen-doped porous carbon composite material is provided, comprising the following steps: providing nitrogen-doped porous carbon, mixing the nitrogen-doped porous carbon, Na2WO4·2H2O, selenium powder, aqueous hydrochloric acid solution, and N2H4·2H2O, and preparing the tungsten diselenide / nitrogen-doped porous carbon composite material by a solvothermal method. The preparation method realizes the in-situ generation of tungsten diselenide in the pores of the nitrogen-doped porous carbon.

[0052] In order to further promote the reaction to generate tungsten diselenide, the acid solution preferably includes any one or more of hydrochloric acid solution, acetic acid solution, and phosphoric acid solution; more preferably, it is a hydrochloric acid solution.

[0053] In order to further promote the dissolution of selenium powder, the auxiliary agent preferably includes any one or more of N2H4·2H2O, carbon disulfide, and quinoline; more preferably, N2H4·2H2O.

[0054] In order to better prepare the tungsten diselenide / nitrogen-doped porous carbon composite material, the reaction temperature of the solvothermal method is preferably 180 to 250° C., and the reaction time of the solvothermal method is 10 to 16 hours.

[0055] Typically but not limiting, the reaction temperature of the solvothermal method is 180°C, 200°C, 220°C, 240°C, 250°C or a range consisting of any two values; the reaction time of the solvothermal method is 10h, 12h, 14h, 16h, 18h or a range consisting of any two values.

[0056] In some typical embodiments, the tungsten diselenide / nitrogen-doped porous carbon composite material is prepared by the following steps: (1) adding Na2WO4·2H2O and selenium powder to deionized water, and ultrasonically treating to promote dispersion of the solution to obtain a primary mixed solution; (2) adding hydrochloric acid aqueous solution, N2H4·2H2O, and nitrogen-doped porous carbon to the primary mixed solution, stirring and ultrasonically treating for multiple cycles to obtain a secondary mixed solution. In order to further promote the reaction to generate tungsten diselenide, the concentration of the hydrochloric acid aqueous solution is preferably 36-38wt%. Multiple stirring and ultrasonic treatments can fully mix the solution to promote uniform dispersion of the solute molecules in the pores of the nitrogen-doped porous carbon, and in the subsequent solvothermal process, the generated tungsten diselenide can be further uniformly distributed in the nitrogen-doped porous carbon, avoiding local agglomeration of tungsten diselenide, and promoting the generated tungsten diselenide / nitrogen-doped porous carbon composite material to have a more stable structure. (3) placing the secondary mixed liquid in a reactor, reacting it in a constant temperature oven for 10 to 16 hours, and setting the reaction temperature to 180 to 250°C. After the reaction is completed, the generated liquid is separated into solid and liquid, and the precipitate is washed with anhydrous ethanol and deionized water. The precipitate is vacuum dried at a drying temperature of 50 to 80°C and a drying time of 2 to 12 hours to obtain a tungsten diselenide / nitrogen-doped porous carbon composite material.

[0057] In order to further increase the generation rate of tungsten diselenide, the molar ratio of Na2WO4·2H2O to selenium powder is preferably 1:1-5.

[0058] Typically but not limiting, the molar ratio of Na2WO4·2H2O to selenium powder is 1:1, 1:2, 1:3, 1:4, 1:5 or any range of two values.

[0059] In order to further improve the inhibitory effect of tungsten diselenide / nitrogen-doped porous carbon composite materials on polysulfides, the mass ratio of Na2WO4·2H2O to nitrogen-doped porous carbon is preferably (5-10):1.

[0060] Typically but not limiting, the mass ratio of Na2WO4·2H2O to nitrogen-doped porous carbon is 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or a range consisting of any two of these values.

[0061] In a third typical embodiment of the present application, a modified diaphragm is provided, which includes a diaphragm, and a modified coating is arranged on the side of the diaphragm close to the positive electrode, and the material of the modified coating includes the tungsten diselenide / nitrogen-doped porous carbon composite material, conductive agent and binder provided in the above-mentioned first typical embodiment or the above-mentioned second typical embodiment.

[0062] A modified coating containing a tungsten diselenide / nitrogen-doped porous carbon composite material is coated on the side of the separator close to the positive electrode to obtain a modified separator. Figure 1 Schematic diagram showing the position of the modified separator in the sodium-sulfur battery and the inhibition of the shuttle effect. Figure 1 Sodium Metal Anode means that sodium metal is the negative electrode, and CB / S means that porous carbon@sulfur is the positive electrode. Figure 1 It can be seen that the polysulfides generated by the positive electrode are adsorbed by the modified diaphragm, which effectively inhibits the shuttle effect caused by the dissolution of polysulfides into the organic electrolyte during the cycle of the room temperature sodium-sulfur battery. Among them, porous carbon can adsorb polysulfides through van der Waals forces and active sites, and the introduction of nitrogen atoms into the lattice of carbon atoms by nitrogen doping can further improve the electronic structure and physicochemical properties of porous carbon, so that nitrogen-doped porous carbon has more active sites and promotes the adsorption of more polysulfides. In addition, tungsten diselenide is filled in the pores of nitrogen-doped porous carbon. Polar tungsten diselenide can form bonds with soluble polysulfides to further inhibit the shuttling of polysulfides. Therefore, the abundant adsorption active sites on the modified diaphragm and the strong interaction with polysulfides effectively improve the chemical properties of the battery.

[0063] In some embodiments, the loading amount of the tungsten diselenide / nitrogen-doped porous carbon composite material on the separator is 0.2-0.6 mg / cm 2When the loading amount of tungsten diselenide / nitrogen-doped porous carbon composite material on the diaphragm is too low, the tungsten diselenide / nitrogen-doped porous carbon composite material cannot form an effective barrier layer and adsorption layer on the diaphragm, and cannot effectively adsorb polysulfides; when the loading amount is too high, the mechanical properties of the modified diaphragm will deteriorate, the internal resistance will increase, and the modified coating will easily fall off from the glass fiber diaphragm, and it will not be able to effectively adsorb polysulfides.

[0064] Typically, but not limiting, the loading amount of tungsten diselenide / nitrogen-doped porous carbon composite on the separator is 0.2 mg / cm 2 , 0.3mg / cm 2 , 0.4mg / cm 2 , 0.5mg / cm 2 , 0.6mg / cm 2 Or a range of any two values.

[0065] In the present application, the material of the separator is a commonly used material in the art, including but not limited to any one or more of glass fiber, polypropylene, and polyethylene. In some embodiments, the material of the separator is glass fiber, and the modified glass fiber separator is coated with a modified coating on one side close to the positive electrode.

[0066] In order to further suppress the shuttle effect of polysulfides in the modified diaphragm, a conductive agent is preferably added to the modified coating; the conductive agent includes any one or more of Super P (conductive carbon black), activated carbon, and acetylene black, and the conductive agent is more preferably Super P.

[0067] In order to further better coat the modified coating on one side of the modified diaphragm, it is preferred to add a binder to the modified coating; the binder includes any one or more of PVDF (polyvinylidene fluoride), CMC (sodium carboxymethyl cellulose), SBR (styrene-butadiene rubber), and the binder is further preferably PVDF (polyvinylidene fluoride).

[0068] In order to further improve the properties of the modified diaphragm, it is preferred that the material of the diaphragm includes at least one of glass fiber, polypropylene, and polyethylene, and it is further preferred that the material of the diaphragm is glass fiber.

[0069] In some embodiments, the mass ratio of tungsten diselenide / nitrogen-doped porous carbon composite material, conductive agent, and binder in the material of the modified coating is (6-8):(1-3):1, so as to further improve the performance of the modified coating and its adhesion on the diaphragm.

[0070] Typically but not limiting, the mass ratio of tungsten diselenide / nitrogen-doped porous carbon composite material, conductive agent, and binder in the modified coating material is, for example, 6:3:1, 7:2:1, 8:1:1, or a range consisting of any two values.

[0071] In the fourth typical embodiment of the present application, a method for preparing a modified diaphragm is provided, wherein a tungsten diselenide / nitrogen-doped porous carbon composite material, a conductive agent, and a binder are mixed and ground, and then dispersed in a solvent to obtain a modified coating slurry; the modified coating slurry is applied to the side of the diaphragm close to the positive electrode, and the solvent is removed to obtain a modified diaphragm. The preparation method of the modified diaphragm is simple to operate and is suitable for industrial production. The solvent removal method includes but is not limited to vacuum drying, and any solvent removal method commonly used in the art can be used. In the present application, the preferred method of vacuum drying is to evaporate and remove the solvent.

[0072] In order to better dissolve the tungsten diselenide / nitrogen-doped porous carbon composite material, the conductive agent, and the binder to prepare a slurry, the preferred solvent includes any one or more of NMP (N-methylpyrrolidone), deionized water, and DMF (dimethylformamide), and NMP (N-methylpyrrolidone) is further preferred.

[0073] In a fifth typical embodiment of the present application, there is also provided a tungsten diselenide / nitrogen-doped porous carbon composite material provided in the first typical embodiment or the second typical embodiment, and a modified diaphragm provided in the third typical embodiment or the fourth typical embodiment for use in a sodium-sulfur battery.

[0074] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.

[0075] Example 1

[0076] (1) Preparation of nitrogen-doped porous carbon:

[0077] Under the protection of argon, the activated carbon was heated to 800°C and kept warm for 1 hour; then it was mixed with potassium hydroxide (mass ratio of 1:1), deionized water was added and stirred to mix evenly, and it was dried in an oven at 80°C to remove moisture to obtain a mixture; the mixture was placed in a tubular furnace for activation treatment, that is, the temperature was raised to an activation temperature of 700°C at 2°C / min in an Ar atmosphere, kept warm for 2 hours, and then cooled to room temperature; 2 mol / L hydrochloric acid solution was slowly added to the cooled product to remove the alkaline substances remaining on the surface, and then it was washed with deionized water to neutrality, and then placed in an oven at 80°C for drying to obtain porous carbon.

[0078] Porous carbon and melamine were placed in a magnetic boat at a weight ratio of 1:5, sealed, and placed in the middle of the first tube furnace for the first heating treatment (heating rate of 2°C / min, holding time of 5h after reaching 850°C), cooled to room temperature, and nitrogen-doped porous carbon was obtained. The specific surface area of ​​nitrogen-doped porous carbon is 269.5m 2 / g, pore volume 0.36cm 3 / g.

[0079] (2) Preparation of tungsten diselenide / nitrogen-doped porous carbon composite materials:

[0080] 0.528g Na2WO4·2H2O and 0.256g selenium powder are added to deionized water and ultrasonically treated for 30 minutes to obtain a primary mixed solution; 10mL of a 36.28wt% hydrochloric acid aqueous solution, 7.35mL N2H4·2H2O, and 60mg of nitrogen-doped porous carbon are added to the primary mixed solution, and the mixture is stirred for 30 minutes and ultrasonically treated for 5 minutes for four times to obtain a secondary mixed solution; the secondary mixed solution is placed in a reactor, reacted in a constant temperature oven at 200°C for 12 hours, the generated liquid is centrifuged, and the precipitate is washed with anhydrous ethanol and deionized water, and then the precipitate is dried at 60°C for 10 hours, and after screening, a tungsten diselenide / nitrogen-doped porous carbon composite material with a particle size range of 0.5 to 1.0μm is obtained.

[0081] (3) Preparation of modified diaphragm:

[0082] The tungsten diselenide / nitrogen-doped porous carbon composite material, Super P and PVDF were mixed in a mass ratio of 7:2:1 and ground, and then 10 mL of NMP was added and stirred to obtain a modified coating slurry. The modified coating slurry was coated on the side of the glass fiber separator close to the positive electrode. The loading amount of the tungsten diselenide / nitrogen-doped porous carbon composite material on the glass fiber separator was 0.4 mg / cm 2 , put it into a vacuum drying oven for drying at a temperature of 80°C and a drying time of 6 hours to obtain a modified glass fiber diaphragm, and cut the modified glass fiber diaphragm into discs for later use. The SEM image of the modified glass fiber diaphragm is shown in Figure 2 shown.

[0083] Example 2

[0084] The difference between Example 2 and Example 1 is that in step (1), the mass ratio of porous carbon to melamine is set to 1:10.

[0085] Example 3

[0086] The difference between Example 3 and Example 1 is that in step (1), the mass ratio of porous carbon to melamine is set to 1:1.

[0087] Example 4

[0088] The difference between Example 4 and Example 1 is that in step (2), the mass ratio of Na2WO4·2H2O to nitrogen-doped porous carbon is set to 5:1.

[0089] Example 5

[0090] The difference between Example 5 and Example 1 is that in step (2), the mass ratio of Na2WO4·2H2O to nitrogen-doped porous carbon is set to 10:1.

[0091] Example 6

[0092] The difference between Example 6 and Example 1 is that the mass ratio of porous carbon to melamine, and the mass ratio of Na2WO4·2H2O to nitrogen-doped porous carbon are adjusted so that the mass ratio of tungsten diselenide and carbon in nitrogen-doped porous carbon is 10:90, and the nitrogen doping amount in the porous carbon composite material is 5 at.%.

[0093] Example 7

[0094] The difference between Example 7 and Example 1 is that the mass ratio of porous carbon to melamine, and the mass ratio of Na2WO4·2H2O to nitrogen-doped porous carbon are adjusted so that the mass ratio of tungsten diselenide and carbon in nitrogen-doped porous carbon is 30:70, and the nitrogen doping amount in the porous carbon composite material is 1 at.%.

[0095] Example 8

[0096] The difference between Example 8 and Example 1 is that in step (3), the loading amount of the tungsten diselenide / nitrogen-doped porous carbon composite material on the glass fiber diaphragm is adjusted so that the loading amount is 0.2 mg / cm 2 .

[0097] Example 9

[0098] The difference between Example 9 and Example 1 is that in step (3), the loading amount of the tungsten diselenide / nitrogen-doped porous carbon composite material on the glass fiber diaphragm is adjusted so that the loading amount is 0.6 mg / cm 2 .

[0099] Example 10

[0100] The difference between Example 10 and Example 1 is that in step (3), the loading amount of the tungsten diselenide / nitrogen-doped porous carbon composite material on the glass fiber diaphragm is adjusted so that the loading amount is 0.05 mg / cm 2 .

[0101] Embodiment 11

[0102] The difference between Example 11 and Example 1 is that in step (3), the loading amount of the tungsten diselenide / nitrogen-doped porous carbon composite material on the glass fiber diaphragm is adjusted so that the loading amount is 1.0 mg / cm 2 .

[0103] Example 12

[0104] The difference between Example 12 and Example 1 is that in step (3), the mass ratio of tungsten diselenide / nitrogen-doped porous carbon composite material, Super P and PVDF is adjusted so that the mass ratio of the three is 6:3:1.

[0105] Embodiment 13

[0106] The difference between Example 13 and Example 1 is that in step (3), the mass ratio of the tungsten diselenide / nitrogen-doped porous carbon composite material, Super P and PVDF is adjusted so that the mass ratio of the three is 8:1:1.

[0107] Embodiment 14

[0108] The difference between Example 14 and Example 1 is that no conductive agent is added when preparing the modified coating slurry in step (3), the tungsten diselenide / nitrogen-doped porous carbon composite material and PVDF are mixed in a mass ratio of 7:1 and then ground, and then NMP is added and stirred to obtain the modified coating slurry.

[0109] Embodiment 15

[0110] The difference between Example 15 and Example 1 is that, in the process of preparing nitrogen-doped porous carbon in step (1), the amount of potassium hydroxide is adjusted so that the surface area of ​​the nitrogen-doped porous carbon is 100 m 2 / g, pore volume 0.12cm 3 / g.

[0111] Example 16

[0112] The difference between Example 16 and Example 1 is that, in the process of preparing nitrogen-doped porous carbon in step (1), the amount of potassium hydroxide is adjusted so that the surface area of ​​the nitrogen-doped porous carbon is 500 m 2 / g, pore volume 0.65cm 3 / g.

[0113] Embodiment 17

[0114] The difference between Example 17 and Example 1 is that, in the process of preparing nitrogen-doped porous carbon in step (1), the amount of potassium hydroxide is adjusted so that the surface area of ​​the nitrogen-doped porous carbon is 50.5 m 2 / g, pore volume 0.10cm 3 / g.

[0115] Embodiment 18

[0116] The difference between Example 18 and Example 1 is that, in the process of preparing nitrogen-doped porous carbon in step (1), the amount of potassium hydroxide is adjusted so that the surface area of ​​the nitrogen-doped porous carbon is 700 m 2 / g, pore volume 0.85cm3 / g.

[0117] Comparative Example 1

[0118] The difference between Comparative Example 1 and Example 1 is that the glass fiber diaphragm in Comparative Example 1 is not coated with the modified coating slurry. The SEM image of the glass fiber diaphragm is as follows: Figure 3 shown.

[0119] Comparative Example 2

[0120] The difference between Comparative Example 2 and Example 1 is that the composite material prepared in Comparative Example 2 contains only nitrogen-doped porous carbon but no tungsten diselenide.

[0121] Comparative Example 3

[0122] The difference between Comparative Example 3 and Example 1 is that the composite material prepared in Comparative Example 3 only contains tungsten diselenide and does not contain nitrogen-doped porous carbon.

[0123] Comparative Example 4

[0124] The difference between Comparative Example 4 and Example 1 is that, in Comparative Example 4, nitrogen doping is not introduced into the porous carbon.

[0125] Comparative Example 5

[0126] The difference between Comparative Example 5 and Example 1 is that in step (2), Comparative Example 5 adjusts the mass ratio of porous carbon to melamine, and the mass ratio of Na2WO4·2H2O to nitrogen-doped porous carbon, so that the mass ratio of tungsten diselenide and carbon in nitrogen-doped porous carbon is 45:55, and the nitrogen doping amount in the porous carbon composite material is 3.3 at.%.

[0127] Comparative Example 6

[0128] The difference between Comparative Example 6 and Example 1 is that in step (2), Comparative Example 6 adjusts the mass ratio of porous carbon to melamine, and the mass ratio of Na2WO4·2H2O to nitrogen-doped porous carbon, so that the mass ratio of tungsten diselenide and carbon in nitrogen-doped porous carbon is 3:97, and the nitrogen doping amount in the porous carbon composite material is 6 at.%.

[0129] Test Example 1

[0130] The tungsten diselenide / nitrogen-doped porous carbon composite materials provided in the embodiment and the comparative example were subjected to XPS elemental analysis (instrument: Thermo ESCALAB 250Xi Spectrophotometer) to test and obtain the contents of tungsten diselenide, nitrogen and carbon. The results are shown in Table 1.

[0131] The specific surface area and pore volume of nitrogen-doped porous carbon were tested using the BET method on an ASAP 2020 nitrogen adsorption-desorption instrument.

[0132] Test Example 2

[0133] The modified diaphragm samples provided in the examples and comparative examples were used for performance testing of sodium-sulfur batteries, and their cycle performance indicators were tested to evaluate their performance in sodium-sulfur battery applications.

[0134] The porous carbon@sulfur (the mass ratio of sulfur to porous carbon is 70:30, the pore size of the porous carbon is 8 nm, and the pore volume is 1.3 cm 3 / g) as the positive electrode, sodium metal as the negative electrode, the electrolyte composition is 1M NaClO4 in EC (ethylene carbonate): PC (propylene carbonate) = 1:1 Vol% with 5% FEC (fluoroethylene carbonate), and assembled with the above modified diaphragm sample into a room temperature sodium-sulfur battery. The obtained room temperature sodium-sulfur battery was tested for 100 charge and discharge cycles at a current density of 0.1C or 0.5C, respectively, to obtain the initial discharge specific capacity at a current density of 0.1C, the discharge specific capacity after 100 cycles at a current density of 0.1C, the initial discharge specific capacity at a current density of 0.5C, and the discharge specific capacity after 100 cycles at a current density of 0.5C. The results are shown in Table 2.

[0135] Test Example 3

[0136] The SEM images of the modified glass fiber diaphragm in Example 1 and the glass fiber diaphragm not coated with the modified coating slurry in Comparative Example 1 were observed by scanning electron microscopy. The results are as follows: Figure 2 , Figure 3 As shown. Figure 2 and Figure 3 It can be seen that compared with the unmodified glass fiber membrane, the surface of the modified glass fiber membrane becomes denser, which is conducive to hindering the passage of polysulfide and thus inhibiting the shuttle effect.

[0137] Table 1

[0138]

[0139]

[0140] In Table 1, “--” means that the contents of tungsten diselenide, nitrogen and carbon were not detected.

[0141] Table 2

[0142]

[0143]

[0144] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0145] From the experimental data of Examples 1-7 and Comparative Examples 1-6, it can be seen that when the mass ratio of tungsten diselenide and carbon in nitrogen-doped porous carbon is (10-30): (90-70), and the nitrogen doping amount in the tungsten diselenide / nitrogen-doped porous carbon composite material is 1-5 at.%, the modified diaphragm sample coated with the tungsten diselenide / nitrogen-doped porous carbon composite material is assembled into a sodium-sulfur battery, and the test shows that it has a higher discharge specific capacity, indicating that the diaphragm is modified by the tungsten diselenide / nitrogen-doped porous carbon composite material, which can inhibit the shuttle effect caused by the dissolution of polysulfide into the organic electrolyte during the cycle of the room temperature sodium-sulfur battery, and significantly improve the electrochemical performance of the room temperature sodium-sulfur battery. When the content of the components in the composite material is changed or any component is missing, the discharge specific capacity is significantly reduced, and the electrochemical performance of the sodium-sulfur battery is reduced.

[0146] It can be seen from the experimental data of Examples 8-11 that when the loading amount of tungsten diselenide / nitrogen-doped porous carbon composite material on the diaphragm is 0.2-0.6 mg / cm 2 When the modified diaphragm sample coated with the tungsten diselenide / nitrogen-doped porous carbon composite material is assembled into a sodium-sulfur battery, the test shows that the discharge specific capacity is high, and the electrochemical performance of the room temperature sodium-sulfur battery is excellent. When the load amount changes, the discharge specific capacity decreases, and the electrochemical performance of the room temperature sodium-sulfur battery decreases.

[0147] It can be seen from the experimental data of Examples 12-14 that when the mass ratio of tungsten diselenide / nitrogen-doped porous carbon composite material, conductive agent, and binder is (6-8): (3-1): 1, the obtained modified diaphragm sample is assembled into a sodium-sulfur battery, and the test shows a high discharge specific capacity, and the electrochemical performance of the room temperature sodium-sulfur battery is excellent. When the mass ratio of the components changes, the discharge specific capacity decreases, and the electrochemical performance of the room temperature sodium-sulfur battery decreases.

[0148] It can be seen from the experimental data of Examples 15-18 that when the specific surface area of ​​nitrogen-doped porous carbon is 100-500 m 2 / g; the pore volume of nitrogen-doped porous carbon is 0.12 cm 3 / g~0.65cm 3 / g, a modified diaphragm sample coated with the tungsten diselenide / nitrogen-doped porous carbon composite material was assembled into a sodium-sulfur battery, and the test showed that the discharge specific capacity was high, and the electrochemical performance of the room temperature sodium-sulfur battery was excellent. When the specific surface area and / or pore volume of the nitrogen-doped porous carbon changed, the discharge specific capacity decreased, and the electrochemical performance of the room temperature sodium-sulfur battery decreased.

[0149] The present application modifies the diaphragm by a tungsten diselenide / nitrogen-doped porous carbon composite material to suppress the shuttle effect caused by the dissolution of polysulfides into the organic electrolyte during the cycle of the room temperature sodium-sulfur battery. The tungsten diselenide / nitrogen-doped porous carbon composite material is filled with tungsten diselenide in the pores of the nitrogen-doped porous carbon, wherein the polar tungsten diselenide can form a bond with the soluble polysulfide to limit the shuttling of the polysulfide; at the same time, the porous carbon adsorbs the polysulfide through the van der Waals force and active sites; and the nitrogen doped in the porous carbon can provide more active sites to adsorb the polysulfide, thereby effectively suppressing the "shuttle effect", effectively reducing the loss of active substances, and significantly enhancing the stability of the battery. By coating the coating material containing the tungsten diselenide / nitrogen-doped porous carbon composite material on the side of the diaphragm close to the positive electrode to obtain a modified diaphragm, the electrochemical performance of the room temperature sodium-sulfur battery can be significantly improved.

[0150] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A tungsten diselenide / nitrogen-doped porous carbon composite material, characterized in that: The tungsten diselenide / nitrogen-doped porous carbon composite material includes nitrogen-doped porous carbon, and the pores of the nitrogen-doped porous carbon are filled with tungsten diselenide; wherein the mass ratio of the tungsten diselenide to the carbon in the nitrogen-doped porous carbon is (10-30): (90-70), and the doping amount of nitrogen in the tungsten diselenide / nitrogen-doped porous carbon composite material is 1-5at.%.

2. The tungsten diselenide / nitrogen-doped porous carbon composite material according to claim 1, characterized in that: The particle size of the tungsten diselenide / nitrogen-doped porous carbon composite material is 0.5-1.0 μm; And / or, the specific surface area of ​​the nitrogen-doped porous carbon is 100 to 500 m 2 / g; the pore volume of the nitrogen-doped porous carbon is 0.12cm 3 / g~0.65cm 3 / g.

3. The tungsten diselenide / nitrogen-doped porous carbon composite material according to claim 1, characterized in that: The method for preparing nitrogen-doped porous carbon comprises the following steps: mixing porous carbon with melamine and performing a heating treatment to obtain the nitrogen-doped porous carbon.

4. The tungsten diselenide / nitrogen-doped porous carbon composite material according to claim 3, characterized in that: The mass ratio of the porous carbon to the melamine is 1:1 to 10; And / or, the temperature of the heating treatment is 800-850° C., and the time of the heating treatment is 4-6 hours.

5. The method for preparing the tungsten diselenide / nitrogen-doped porous carbon composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Providing nitrogen-doped porous carbon, mixing the nitrogen-doped porous carbon, Na2WO4·2H2O, selenium powder, acid solution, and additives, and preparing the tungsten diselenide / nitrogen-doped porous carbon composite material by a solvothermal method; Preferably, the acid solution includes at least one of a hydrochloric acid solution, an acetic acid solution, and a phosphoric acid solution; more preferably, a hydrochloric acid solution; Preferably, the auxiliary agent includes at least one of N2H4·2H2O, carbon disulfide, and quinoline; more preferably N2H4·2H2O; Preferably, the reaction temperature of the solvothermal method is 180 to 250° C., and the reaction time of the solvothermal method is 10 to 16 hours.

6. The preparation method according to claim 5, characterized in that: The molar ratio of Na2WO4·2H2O to selenium powder is 1:1-5; And / or, the mass ratio of Na2WO4·2H2O to the nitrogen-doped porous carbon is (5-10):

1.

7. A modified diaphragm, characterized in that: The modified diaphragm comprises a diaphragm, a modified coating is provided on one side of the diaphragm close to the positive electrode, and the material of the modified coating comprises the tungsten diselenide / nitrogen-doped porous carbon composite material, a conductive agent and a binder as described in any one of claims 1 to 6; Preferably, the loading amount of the tungsten diselenide / nitrogen-doped porous carbon composite material on the diaphragm is 0.2-0.6 mg / cm 2 .

8. The modified diaphragm according to claim 7, characterized in that: The conductive agent includes at least one of Super P, activated carbon, and acetylene black, and preferably the conductive agent is Super P; And / or, the binder comprises at least one of PVDF, CMC, and SBR, preferably the binder is PVDF; And / or, the material of the diaphragm includes at least one of glass fiber, polypropylene, and polyethylene; preferably, the material of the diaphragm is glass fiber; And / or, the mass ratio of the tungsten diselenide / nitrogen-doped porous carbon composite material, the conductive agent, and the binder is (6-8):(3-1):

1.

9. The method for preparing the modified diaphragm according to claim 7 or 8, characterized in that: The preparation method comprises the following steps: The tungsten diselenide / nitrogen-doped porous carbon composite material, the conductive agent, and the binder are mixed and ground, and then dispersed in a solvent to obtain a modified coating slurry; the modified coating slurry is applied to the side of the diaphragm close to the positive electrode, and the solvent is removed to obtain the modified diaphragm; Preferably, the solvent includes at least one of NMP, deionized water, and DMF, more preferably NMP.

10. Use of the tungsten diselenide / nitrogen-doped porous carbon composite material according to any one of claims 1 to 6 or the modified separator according to any one of claims 7 to 9 in a sodium-sulfur battery.

Citation Information

Patent Citations

  • Molybdenum (tungsten) diselenide (disulfide) / carbon composite material as well as preparation method and application thereof

    CN106816602A

  • Synthetic method and application of tungsten selenide-collagen derived porous carbon composite sodium ion battery anode material with excellent performance

    CN110265637A

  • Metal sulfur selenide / carbon composite hollow nanosphere as well as preparation method and application thereof

    CN118588896A

  • A new class of electrocatalysts

    US20170342578A1

  • Two dimensional (2D) transition metal dichalcogenide (TMD) materials and alloys as catalysts for cathode in lithium sulfur (li-s) batteries

    US20210313576A1